HUMANS IN ISLAMIC HUMANISTIC EDUCATION PERSPECTIVE - Robbani, A. Syahid; Maragustam, Maragustam (Jurnal Tatsqif, 2022)
This research aims to examine the nature of humans, starting from the essence that exists in humans, the purpose of life or the purpose of its creation, the potentials possessed, and their implications for humanistic education. This research becomes important because humanistic education based on the principle of humanity and the interests of fellow human beings seek to answer the problems that exist in the world of education, especially those related to the development of learners' potential through warm interaction and harmonious communication. This research is a type of literature research with a qualitative approach. The data is obtained through sources in books and scientific articles related to the topic. This study shows that God equips humans with various potentials and characteristics to fulfill all the tasks and obligations carried out by humans. The potential and characteristics given to humans also distinguish them from other creatures. In addition, these potentials also need to be concerned with determining the direction and purpose of education. One educational concept that gives full attention to these potentials is humanistic education by forming a warm interaction and harmonious communication between educators and learners.